2007
DOI: 10.1177/145749690709600109
|View full text |Cite
|
Sign up to set email alerts
|

Immunonutrition in Elective Gastrointestinal Surgery Patients

Abstract: Background: previous trials have shown that perioperative immunonutrition could protect patients from infectious complications after gastrointestinal cancer operations. the purpose of this study was to determine whether perioperative immunonutrition decreases postoperative morbidity,especially infection complications, mortality and length of hospital stay in patients undergoing major gastrointestinal tract surgery.Methods: one hundred patients with ap lanned elective operation for benign or malignant gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 26 publications
1
38
0
7
Order By: Relevance
“…These findings have been confirmed in patient undergoing oesophagectomy (12) for oesophageal cancer, however other reports suggest peri-operative immunonutrition for patients undergoing major gastrointestinal surgery not to be beneficial (13) in terms of complication rates or length of hospital stay. These clinical trials tended to be on heterogeneous patient groups and involved different combinations of feed.…”
Section: Introductionsupporting
confidence: 67%
“…These findings have been confirmed in patient undergoing oesophagectomy (12) for oesophageal cancer, however other reports suggest peri-operative immunonutrition for patients undergoing major gastrointestinal surgery not to be beneficial (13) in terms of complication rates or length of hospital stay. These clinical trials tended to be on heterogeneous patient groups and involved different combinations of feed.…”
Section: Introductionsupporting
confidence: 67%
“…A further trial using the same supplement for 5 d pre-and post-operatively found no significant differences in infectious complications, mortality or length of stay when compared with a group receiving no nutrition support (20) .…”
Section: Immunonutritionmentioning
confidence: 93%
“…O conceito implica em indicar-se adequadamente cada imunonutriente, tais como glutamina, selênio, óleo de peixe (ácidos graxos -3) e arginina, a cada situação clínica, entre elas desnutrição, queimaduras, trauma, pacientes em estado crítico ou em síndrome de estresse respiratório agudo. Basearam sua argumentação no fato que os diversos estudos apresentados até o momento incorrem em erros metodológicos diversos, como seleção inadequada da amostra para estudo, uso de produtos para o estudo que associam diversos imunonutrientes 2,4,13,17,28,35,38,43 . Nesta linha de raciocínio, alguns autores estão buscando limitar o foco da amostra.…”
Section: Discussionunclassified